Resilience Across Developmental Transitions: A Systematic Literature Review from Adolescence to Adulthood - Titin Kholisna; Sri Handayani (Journal of Education and Pedagogy, 2026)
The aims study is to systematically review the literature on resilience across developmental transitions and to develop an integrative framework. This study employed a systematic literature review approach following PRISMA 2020 guidelines. Literature was collected from Scopus, Web of Science, PubMed, and Google Scholar within the publication period of 2015–2025. A total of 842 records were identified, and 28 articles met the inclusion criteria for final analysis.The results identified six main themes: resilience as a longitudinal developmental process, the interaction of risk and protective factors, psychological mechanisms with emphasis on emotional intelligence, neurobiological dimensions of resilience, effectiveness of resilience-based interventions, and the role of social support and identity in emerging adulthood. These findings indicate that resilience is a dynamic adaptive system shaped by the interaction of multidimensional factors over time.This study contributes to the development of a biopsychosocial framework of resilience and provides practical implications for designing resilience-based interventions among adolescents and emerging adults.